PENGARUH LINGKUNGAN KERJA DAN KOMPETENSI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PG PRADJEKAN BONDOWOSO DENGAN PRESTASI KERJA SEBAGAI VARIABEL INTERVENING - Efendi, Riskon; Hamdun, Edy Kusnadi; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The results of direct influence hypothesis testing using the Smart PLS 3.0 application, work environment has a significant positive effect on job performance (H1 accepted), work competence has a positive but insignificant effect on job performance (H2 rejected), work environment has a positive but insignificant effect on job satisfaction (H3 rejected), work competence has a positive but insignificant effect on job satisfaction (H4 rejected), work achievement has a significant positive effect on job satisfaction (H5 accepted), work environment has a positive but insignificant effect on job satisfaction through work achievement (H6 rejected) and work competence has a positive but insignificant effect on job satisfaction through work achievement (H7 rejected).